Effect of Pullback Speed and the Distance between the Skin and Vein on the Performance of Endovenous Laser Treatment by Numerical Simulation - Alireza Rezvani-sharif (Iranian Journal of Medical Physics, 2018)
Introduction: Endovenous laser treatment (ELT) is a new treatment method for the reflux of the great saphenous vein. A successful ELT is dependent on the selection of optimum parameters required to achieve optimal vein damage while avoiding side effects including skin burns. The mathematical modeling of ELT can be used to understand the process of ELT. This study was conducted to examine the effect of laser pullback speed and the distance between the vein and skin on the performance of ELT. Material and Methods: The finite element method was used to develop optical-thermal damage models and simulate the process of ELT process. Firstly, light distribution was modeled using the diffusion approximation of the transport theory. On the second step, temperature rise was determined by solving the bioheat equation. Considering the temperature field, the extension of laser-induced tissue damage was estimated using Arrhenius model. Results: Regarding the results, pullback speed and the distance between the vein and the skin distance can affect the process of ELT. Moreover, the pullback speed of 1 mm/s, 2 mm/s, and 4mm/s were suitable for the treatment of varicose veins located in a depth of 15 mm, 10 mm, and 5 mm, respectively. Conclusion: In the ELT method, the pullback speed should be determined considering the geometry of the varicose vein segments, especially the distance between the skin and vein.